الشخصيات و محمولات الهجرة في رواية سفينة نوح لخالد الخميسي (بحث مُستلّ من رسالة ماجستير) - فؤاد, المشرف: أ . د . نيان نوشيروان; كاظم, الباحثة: سعاد جواد (Sulaimani Journal for Humanities, 2023)
Migration has become an issue related to human rights and social development at the global and regional levels. Migration is linked to economic, political, social and even natural changes. Migration takes many forms. Migration can take place illegally. Or enter legally and stay even after the end of the residence, both ways happened with the characters of our novel.. In our study, we shed light on the issue of migration and its literary and artistic implications that reflected the social, political and economic reality in Egypt, from which the events of our novel "Noah's ship " were launched. By Khaled Al-Khamisi, by presenting the characters and their dimensions, where the characters of the novel were presented in two ways, namely the news method and the manifestation method, and each method was divided in turn into two parts and we explained them in detail in the first topic, and what we dealt with in the second section of this study was about the dimensions of the novelist character, which is the material dimension describes The appearance of the personality and the social dimension, which shows the status of the character while she is in the middle of society. As for the psychological dimension, it explains the internal motivations of the personality, as these dimensions formed the aspects of the characters of our novel . We have relied on the descriptive analytical method, because it is one of the most important and most common methods of scientific research in analysis. And because it studies reality in a precise way, through it, the researcher identifies the problems and causes that led to the occurrence of this phenomenon and finds solutions to them.
Keywords: Keywords Migration and its repercussions; introduction of personality; dimensions of personality; importance of personality